2017
DOI: 10.1093/jxb/erx363
|View full text |Cite
|
Sign up to set email alerts
|

Exocyst and autophagy-related membrane trafficking in plants

Abstract: Endomembrane traffic in eukaryotic cells functions partially as a means of communication; delivery of membrane in one direction has to be balanced with a reduction at the other end. This effect is typically the case during the defence against pathogens. To combat pathogens, cellular growth and differentiation are suppressed, while endomembrane traffic is poised towards limiting the pathogen attack. The octameric exocyst vesicle-tethering complex was originally discovered as a factor facilitating vesicle-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 109 publications
0
46
0
Order By: Relevance
“…Autophagy is integrated tightly with endocytic and exocytic pathways and the trafficking routes to the vacuole (Deretic et al, 2012;Spitzer et al, 2015;Pečenková et al, 2017). Thus, it is probable that putative modulators of autophagy identified in the previous phases of the screen influence the endomembrane system and thus activate or inhibit autophagy indirectly and have significant off-target effects, as was recently shown for some characterized compounds (Wu et al, 2010; Mauthe et al, 2018).…”
Section: Phase 4: Specificity Checkmentioning
confidence: 86%
“…Autophagy is integrated tightly with endocytic and exocytic pathways and the trafficking routes to the vacuole (Deretic et al, 2012;Spitzer et al, 2015;Pečenková et al, 2017). Thus, it is probable that putative modulators of autophagy identified in the previous phases of the screen influence the endomembrane system and thus activate or inhibit autophagy indirectly and have significant off-target effects, as was recently shown for some characterized compounds (Wu et al, 2010; Mauthe et al, 2018).…”
Section: Phase 4: Specificity Checkmentioning
confidence: 86%
“…EXO70s are subunits of the octomeric exocyst complex, which is involved in exocytosis and other cellular trafficking processes. Recent studies have shown that EXO70 paralogs could also play roles in autophagy 17, 50, 51 . EXO70D3 interacted with ARR5 D87E , but not with a wild-type ARR5 or ARR5 D87A bait in a yeast two-hybrid assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this, EXO70B1 colocalizes with ATG8 proteins in autophagosomes and disruption of EXO70B1 resulted in fewer vacuolar autophagic vesicles 17 . Multiple other EXO70 isoforms also contain AIM domains 18, 19 , suggesting that they may also act as receptors for the autophagic regulation of various cellular components.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is tightly integrated with endo- and exocytic pathways and the trafficking routes to the vacuole 2426 . Thus, it is probable that putative modulators of autophagy identified in the previous phases of the screen might influence the endomembrane system and thus activate or inhibit autophagy indirectly and have significant off-target effects, as it has been recently shown for some of the known compounds 9, 10 .…”
Section: Resultsmentioning
confidence: 99%
“…While assays of the first three phases are focused on assessing the drug effect on autophagy activity, the fourth phase puts the drug activity into a broader context. Due to overwhelming complexity of the network, it is frequently overlooked that autophagy is an integral part of the endomembrane trafficking system 26, 29, 30 . The assays in the fourth phase help to identify treatment conditions under which the candidate drugs significantly influence autophagy activity while not causing detectable aberrations in other components of the trafficking machinery.…”
Section: Discussionmentioning
confidence: 99%